Transcriptome and genome-wide analysis of the potential role of SKP1 gene family in the development of floral organs of two related species of Allium fistulosum - Wang, Ning; Lin, Chenyi; Yang, Zhongmin; Zhao, Dan (Frontiers in Plant Science, 2024)
Allium fistulosum is an important plant germplasm resource, rich in nutrients and possessing unique medicinal value. However, due to its small floral organs, low seed setting rate of a single flower, high cost of artificial emasculation, and artificial pollination, the use of male sterile lines to prepare Allium hybrids has become a common choice. In this study, A. fistulosum var. viviparum Makino and A. galanthum were used as materials to study the regulation mechanism of anther development, aiming to provide a reference for male sterility. Through transcriptome differential gene screening and genome-wide bioinformatics analysis, 34 SKP1 (S-phase kinase-associated protein 1) genes (AfSKP1-1 to AfSKP1-34) were identified in the whole genome of A. fistulosum. The AfSKP1 genes are unevenly distributed on eight chromosomes. Furthermore, two pairs of collinear relationships are evident among family members, and fragment replication events between AfSKP1 genes have been identified. The phylogenetic tree analysis demonstrated that the AfSKP1, AtSKP1, OsSKP1, and SlSKP1 genes were clustered into six groups, exhibiting a gene structure analogous to that observed in members of an evolutionary classification. A combination of gene structure and phylogenetic analysis revealed the presence of cis-acting elements associated with growth, hormone regulation, and stress response within the AfSKP1 genes. Furthermore, expression analysis demonstrated that the AfSKP1 genes exhibited differential expression patterns across various tissues of A.fistulosum. The tissue-specific expression of the AfSKP1 gene was verified by Real-Time PCR. A comparison of the two materials revealed significant differences in the expression of the AfSKP1-8 gene in floral buds, the AfSKP1-11 gene in inflorescence meristems, and the AfSKP1-14 gene in inflorescence meristems, scapes, and floral buds. The results indicated that the three genes may be involved in anther development, thereby providing a theoretical basis for further study of floral organ development and pollen development in AfSKP1 family members.